Perancangan Desain Antarmuka Aplikasi Soul Notes dengan Metode Design Thinking Berbasis Mobile - Purnami, Ni Komang; Rahayuda, I Gede Surya (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 3 No 1 (2024): JNATIA Vol. 3, No. 1, November 2024, 2024)
This study aimed to design an interface for the Soul Notes application using design thinking methodology, focusing on mobile-based applications. The study employed a qualitative approach, involving 5 participants who were asked to use the application and provide feedback. The results showed that the participants found the application easy to use and appreciated its features, such as mood tracking and relaxation techniques. The study also found that the participants valued the application's ability to provide a platform for expressing emotions freely and securely. The results of the study were analyzed using the Single Ease Question (SEQ) method, which indicated a high level of ease of use, with an average score of 6.52 out of 7. The study's findings suggest that the Soul Notes application can effectively support mental well-being and emotional management, and that its design should prioritize user experience and security.